1983
DOI: 10.2307/3429534
|View full text |Cite
|
Sign up to set email alerts
|

Promotion in Urinary Bladder Carcinogenesis

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) and Brogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Tryptophan metabolites have also been regarded as promoter in carcinogenesis in the initiator-promoter model [Cohen, 1983]. Bryan and Springberg [1966] demonstrated that the administration of the 8-methyl ether of XA administered in a cholesterol pellet significantly increased the incidence of bladder tumors compared to the cholesterol pellet alone.…”
Section: Tryptophan or Its Metabolites As Promotersmentioning
confidence: 99%
“…Tryptophan metabolites have also been regarded as promoter in carcinogenesis in the initiator-promoter model [Cohen, 1983]. Bryan and Springberg [1966] demonstrated that the administration of the 8-methyl ether of XA administered in a cholesterol pellet significantly increased the incidence of bladder tumors compared to the cholesterol pellet alone.…”
Section: Tryptophan or Its Metabolites As Promotersmentioning
confidence: 99%
“…Extensive experimental efforts have successfully identified several bladder specific carcinogens in rodent species (9,10,50,53). A continuum of stages in urinary bladder carcinogenesis has been established.…”
Section: Discussionmentioning
confidence: 99%
“…Neoplastic processes typically begin with simple hyperplasia, progress to papillary or nodular (PN) hyperplasia, and sometimes papilloma and invasive carcinomas. The model of initiation-promotion is also relevant to urinary bladder carcinogenesis (10). Observations of experimental urinary bladder carcinogenesis have suggested that 2 types of simple hyperplasia may exist, one reversible and the other nonreversible (20,50).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations